Research on the economic prospects of forming the Ukrainian ethnic network - Sedliar, Diana; Sedliar, Mykhailo (Technology audit and production reserves, 2025)
The object of research is the ethnic network – a new phenomenon of the globalized world. The paper explores the possibilities of forming a Ukrainian ethnic network in the conditions of forced migration caused by a full-scale invasion. When studying this issue, the essence of the “bamboo network” (ethnic network) or, so-called, Oversea Chinese Business Networks (OCBN) is clarified, its significance in the economic development of the People's Republic of China. Using the example of China, the prerequisites for the formation of the “bamboo network” are identified. These include: the formation of permanent national centers within certain territorial boundaries through permanent emigration; the formation of close ties with the mother state; the presence of economic and political ties between countries. It is also investigated that important prerequisites are the presence or absence of a dominant ideology and nationalist idea in the recipient country; the formation of an entrepreneurial culture and the presence of entrepreneurial abilities in migrants. The work draws attention to the level of cultural, spiritual and educational development of emigrants and explores the role of social capital, as it significantly affects the formation of an ethnic network. The work summarizes the challenges of migration faced by donor countries, recipient countries and migrants in particular; identifies the features of each wave of Ukrainian migration; examines the portrait of Ukrainian migrant. It also identifies factors that hindered the construction of Ukrainian ethnic network during each of the migration waves, despite the significant centers of Ukrainian migrants abroad. Based on the research, the prospects for the development of an ethnic network at the present stage and in the future were analyzed, and the importance of the state as the main actor in the process of establishing relationships with Ukrainian migrants abroad was substantiated. The results of this research are important for countries facing significant population outflows caused by migration, as they will allow to consider ethnic networks as one of the factors that can reduce the negative impact of migration on the economy of the donor country.